Viscous second gradient porous materials for bones reconstructed with bio-resorbable grafts. (May 2017) - Giorgio, Ivan; Andreaus, Ugo; dell'Isola, Francesco; Lekszycki, Tomasz
Abstract: It is well known that size effects play an important role in the mechanical behavior of bone tissues at different scales. In this paper we propose a second gradient model for accounting these effects in a visco-poro-elastic material and present some sample applications where bone is coupled with bioresorbable artificial materials of the kind used in reconstructing surgery.